Developing Supplementary Book for Constructing Tests with Minimum Competency Assessment for Elementary Schools Teachers - Sigit Priatmoko; Wiku Aji Sugiri; Agus Mukti Wibowo (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThe government through the Ministry of Education and Culture launched a new policy that was quite controversial, abolishing the National Examination and replacing it with a new assessment mechanism, namely the Minimum Competency Assessment (Asesmen Kompetensi Minimum, abbreviated as AKM). The implementation of AKM has elicited various responses from schools, teachers, and the community. One of the responses that emerged was confusion regarding the concepts, mechanisms, and forms of questions in the AKM. This study aims to answer these issues, by developing a supplementary book for preparing AKM-based questions. This study is developmental research by adapting the Borg and Gall model. There were four stages in this study, including planning, developing, try-out, and dissemination. Data collection technique used questionnaires, interviews, and observations. Quantitative data from the questionnaire were analysed using percentage analysis techniques. While the qualitative data used were descriptive analysis techniques. Â Based on the results of the validation and try-out had been carried out, this supplementary book can be said to be valid and worthy of distribution. The validity test and try-out of prospective users showed that the product that had been developed provides benefits for teachers. The supplementary book for preparing AKM-based questions is a product that can provide information about technical steps for teachers in developing learning evaluation models. However, some improvements still need to be made following the suggestions obtained from the validators and potential users.Keywords: minimum competency assessment, supplementary book, teacher, elementary school.Â AbstrakPemerintah melalui Kementerian Pendidikan dan Kebudayaan meluncurkan kebijakan baru yang cukup kontroversial, yaitu meniadakan Ujian Nasional dan menggantinya dengan mekanisme penilaian baru, yaitu Asesmen Kompetensi Minimum (AKM). Implementasi AKM menuai berbagai tanggapan dari pihak sekolah, guru, dan masyarakat. Salah satu tanggapan yang muncul adalah kebingungan mengenai konsep, mekanisme, dan bentuk soal dalam AKM. Penelitian ini bertujuan untuk menjawab permasalahan tersebut, dengan mengembangkan buku pelengkap penyusunan soal berbasis AKM. Penelitian ini merupakan penelitian pengembangan dengan mengadaptasi model Borg and Gall. Ada empat tahapan dalam penelitian ini, yaitu perencanaan, pengembangan, uji coba, dan diseminasi. Pengumpulan data menggunakan angket, wawancara, dan observasi. Data kuantitatif dari kuesioner dianalisis dengan menggunakan teknik analisis persentase. Sedangkan data kualitatif dianalisis dengan menggunakan teknik analisis deskriptif. Berdasarkan hasil validasi dan uji coba yang telah dilakukan, maka buku pelengkap ini dapat dikatakan valid dan layak edar. Uji validitas dan uji coba calon pengguna menunjukkan bahwa produk yang dikembangkan memberikan manfaat bagi guru. Buku pelengkap penyusunan soal berbasis AKM merupakan produk yang dapat memberikan informasi tentang langkah-langkah teknis bagi guru dalam mengembangkan model evaluasi pembelajaran. Namun demikian, beberapa perbaikan masih perlu dilakukan mengikuti saran yang diperoleh dari validator dan calon pengguna.Kata kunci: asesmen kompetensi minimum, buku suplemen, guru, sekolah dasar.